Endopancreatic Bile Duct Cholangiocarcinoma in a Patient with Peutz-Jeghers Syndrome - Charalabopoulos, Alexandros K. (Hindawi Publishing Corporation, 2011)
Peutz-Jeghers syndrome is a rare autosomal dominant inherited disease characterized by a special type of hamartomatous gastrointestinal polyps combined with mucocutaneous melanin pigmentations. Patients with the syndrome have a high risk of developing neoplasia, with colon, small bowel, and stomach being the most common gastrointestinal sites. Herein, we present the occurrence of a rare tumor in patients with Peutz-Jeghers syndrome; a cholangiocarcinoma of the endopancreatic bile duct. A minireview is also presented. It can be concluded that cholangiocarcinoma remains a possible diagnosis in PJS patients, as in others that present with biliary obstruction. PJS patients may be at higher risk than others in view of their propensity for malignancy.